2007
DOI: 10.1158/0008-5472.can-06-3075
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Activation of the JAK/STAT, PI3K/AKT, and ERK Signaling Is Involved in Leptin-Mediated Promotion of Invasion and Migration of Hepatocellular Carcinoma Cells

Abstract: Various epidemiologic studies have shown that obesity is associated with hepatocellular carcinoma. Leptin, the key player in the regulation of energy balance and body weight control, also acts as a growth factor on certain organs in both normal and disease states. It is plausible that leptin acts to promote hepatocellular carcinogenesis directly affecting malignant properties of liver cancer cells. However, a direct role for leptin in hepatocellular carcinoma has not been shown. In this study, we analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
386
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(405 citation statements)
references
References 54 publications
(89 reference statements)
17
386
0
2
Order By: Relevance
“…To our knowledge, the activation of all three (PI3K/Akt, JAK/STAT, and ERK) pathways in neural stem cells in response to LIF signaling has not been reported previously although concomitant activation of these three pathways have been demonstrated in carcinoma cells where they are involved in promotion of growth, invasion, and migration [84,85]. Here, we have shown that, during differentiation of NP cells, LIF activated PI3K/AKT as well as STAT3 signaling (Fig.…”
Section: Signaling Pathways Activated By Lifsupporting
confidence: 50%
“…To our knowledge, the activation of all three (PI3K/Akt, JAK/STAT, and ERK) pathways in neural stem cells in response to LIF signaling has not been reported previously although concomitant activation of these three pathways have been demonstrated in carcinoma cells where they are involved in promotion of growth, invasion, and migration [84,85]. Here, we have shown that, during differentiation of NP cells, LIF activated PI3K/AKT as well as STAT3 signaling (Fig.…”
Section: Signaling Pathways Activated By Lifsupporting
confidence: 50%
“…In this study, we found that malignant C6 glioma cells indeed expressed more leptin and leptin receptor than non-malignant astrocytes RBA1 and NRA, indicating that leptin and/or leptin receptor play a significant role in neoplastic cells. It has been reported that leptin increases the migration and invasion of hepatocellular carcinoma cells and prostate cancer cells (Frankenberry et al 2004;Saxena et al 2007). Here we found that exogenous application of human recombinant leptin enhanced the migration and invasion ability of C6 glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stromal cells derived from endometriotic lesions express significantly high amounts of leptin under both normoxic and hypoxic conditions (44.3 ± 11.8 pg/ml and 191.5 ± 31.4 pg/ml, respectively) (Wu et al 2007). To take obesity as 20 GLIA-00145-2008 another example, plasma leptin is an excellent index of obesity and correlated with some obesity-related diseases, such as diabetes, coronary heart disease, and obesity-linked carcinoma (Sader et al 2003;Saxena et al 2007). The extracellular space is quite small so that the local extracellular concentration of leptin may reach a much higher concentration in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pill-induced esophagitis and reflux esophagitis account for more than 1/5 th and 2/3 rd esophageal ulceration cases, respectively [18]. Recent reports suggest that intraepithelial eosinophil infiltration within the esophagus is induced throughout multiple signaling pathways, including extracellular signal-related kinase (ERK) [19][20][21], leptin [22] and leptin signaling-related proteins, such as the signal transducer and activator of transcription 3 (STAT3) and the mammalian target of rapamycin (mTOR) [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%